Distribution of high‐risk α‐genus human papillomavirus genotypes impacts cutaneous neoplasms. (10th April 2019) - Aoki, R.; Clanner‐Engelshofen, B.M.; Charnowski, S.; Ruzicka, T.; Reinholz, M.
Abstract: Background: High‐risk α‐genus human papillomaviruses (α‐HPVs) are linked to cervical and genital carcinomas; however, their correlation with cutaneous squamous cell carcinoma (cuSCC) or premalignant skin lesions remains controversial. Objective: We evaluated the contribution of high‐risk α‐HPV to the occurrence of cuSCC, Bowen's disease and actinic keratosis (AK), and the distribution of high‐risk α‐HPV genotypes in these cutaneous tumours. Methods: HPV genotypes were determined using a commercial PCR‐based microarray on skin tissue samples collected from 76 [38 young (<60 years) and 38 elderly (>60 years)] cuSCC, 34 Bowen's disease, 48 AK patients and 10 young controls. Associations between α‐HPV prevalence and relevant risk factors were analysed. Results: High‐risk α‐HPV was more frequently detected in cuSCC patients (57.9%) than in the patients with Bowen's disease (38.2%), AK (0.0%) and control patients (10.0%). The high‐risk α‐HPV prevalence was higher in young than in elderly cuSCC patients (65.8% vs. 50.0%, P = 0.031). The most common HPV type was 16, present in 90.9% of all HPV‐carrying cuSCC patients. Multiple infections with different high‐risk α‐HPV types were found in 20.5% of HPV‐related cuSCC, whereas only single infection with type 16 was found in Bowen's disease. Although sun exposure is known as a major risk factor for cuSCC, high‐risk α‐HPVs were more frequently found in non‐exposed sites rather than in sun‐exposed sites of cuSCC. Conclusion: Multiple infections, as well as single infection with high‐risk α‐HPV may link to cuSCC. In spite of the involvement of high‐risk α‐HPV at high levels in cuSCC and Bowen's disease, no high‐risk α‐HPV was detected in AK patients, suggesting that Bowen's disease rather than AK might be involved in the development of HPV‐related cuSCC as a precursor.